Influence of auxochrome group in disperse dyes bearing azo groups as chromophore center in the biotransformation and molecular docking prediction by reductase enzyme: Implications and assessment for environmental toxicity of xenobiotics - Franco, Jefferson Honorio [UNESP]; da Silva, Bianca F. [UNESP]; Dias, Elisangela Franciscon G.; de Castro, Alexandre A.; Ramalho, Teodorico C.; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier, 2018)
Synthetic azo dyes have increasingly become a matter of great concern as a result of the genotoxic and mutagenic potential of the products derived from azo dye biotransformation. This work evaluates the manner in which reducing enzymes produced by Escherichia coli (E. coli) act on three disperse dyes bearing azo groups, namely Disperse Red 73 (DR 73), Disperse Red 78 (DR 78), and Disperse Red 167 (DR 167). UV–Vis spectrophotometry, high-performance liquid chromatography with diode array detector (HPLC-DAD), and liquid chromatography mass spectrometry (LC-MS/MS) were applied towards the identification of the main products. Seven days of incubation of the azo dyes with the tested enzymes yielded a completely bleached solution. 3–4-Aminophenyl-ethyl-amino-propanitrile was detected following the biotransformation of both DR 73 and DR 78. 4-Nitroaniline and 2-chloro-4-nitroaniline were detected upon the biotransformation of DR 73 and DR 78, respectively. The main products derived from the biotransformation of DR 167 were dimethyl 3,3′-3-acetamido-4-aminophenyl-azanedyl-dipropanoate and 2-chloro-4-nitroaniline. The results imply that DR 73 lost the CN- substituent during the biotransformation. Furthermore, theoretical calculations were also carried out aiming at evaluating the interaction and reactivity of these compounds with DNA. Taken together, the results indicate that DR 73, DR 78, and DR 167 pose health risks and serious threats to both human beings and the environment at large as their biotransformation produces harmful compounds such as amines, which have been widely condemned by the International Agency for Research on Cancer.
Keywords: Azoreductase; Biotransformation; Escherichia coli; Mass spectrometry; Textile dye